2022
DOI: 10.55576/job.v2i2.13
|View full text |Cite
|
Sign up to set email alerts
|

H-Index Predicts Academic Rank Among Full-time Academic Orthopaedic Trauma Surgeons Affiliated with Fellowship Programs

Abstract: Objectives: The purpose was to investigate the association between Hirsch index (H-index) and academic rank among orthopaedic trauma surgeons affiliated with Orthopaedic Trauma Association (OTA) and Accreditation Council for Graduate Medical Education (ACGME) fellowship programs with academic appointments. Additional variables investigated included total number of publications and training program affiliation. Design: Database review. Participants: Orthopaedic trauma surgery faculty members at OTA and ACGME or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…While the h-index is used worldwide for measuring a physician’s publication productivity, it has limitations and has received criticism from several corners, which needs to be considered. It is important to note that a single metric can only provide a rough approximation of an individual’s overall profile [ 33 , 36 ]. Additionally, if a full professor has not published much over many years, their h-index may still remain the same as that of a younger professor who has published a few highly cited articles.…”
Section: Discussionmentioning
confidence: 99%
“…While the h-index is used worldwide for measuring a physician’s publication productivity, it has limitations and has received criticism from several corners, which needs to be considered. It is important to note that a single metric can only provide a rough approximation of an individual’s overall profile [ 33 , 36 ]. Additionally, if a full professor has not published much over many years, their h-index may still remain the same as that of a younger professor who has published a few highly cited articles.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, an investigation of orthopaedic trauma surgeons performed by Simson et al. 11 found that a strong correlation exists between the total number of publications, citations, and H-index and a higher academic rank. In addition, few studies highlight sex and racial disparities present in orthopaedic surgery, along with the potential impacts such disparities have on the field.…”
mentioning
confidence: 99%